Knowledge on uterine prolapse among married women of reproductive age in Nepal - Shrestha B; Devkota B; Khadka BB; Choulagai B; Pahari DP; Onta S; Petzold M; Krettek A (Dove Medical Press, 2014)
Binjwala Shrestha,1,2 Bhimsen Devkota,3,4 Badri Bahadur Khadka,5 Bishnu Choulagai,1,2 Durga Prasad Pahari,1 Sharad Onta,1 Max Petzold,6 Alexandra Krettek2,7 1Department of Community Medicine and Public Health, Institute of Medicine, Tribhuvan University, Kathmandu, Nepal; 2Department of Internal Medicine and Clinical Nutrition, Institute of Medicine, Sahlgrenska Academy at University of Gothenburg, Sweden; 3Development Resource Centre, Kathmandu, Nepal; 4Institute of Education, Tribhuvan University, Kathmandu, Nepal; 5National Health Education Information and Communication Centre, Ministry of Health and Population, Government of Nepal, Kathmandu, Nepal; 6Akademistatistik – Centre for Applied Biostatistics, Occupational and Environmental Medicine, University of Gothenburg, Sweden; 7Nordic School of Public Health NHV, Gothenburg, Sweden Background: Uterine prolapse (UP), which affects about 10% of women of reproductive age in Nepal, is the most frequently reported cause of poor health in women of reproductive age and postmenopausal women. Currently, women's awareness of UP is unknown, and attempts to unravel the UP problem are inadequate. This study aims to assess UP knowledge among married reproductive women, and determine the association between UP knowledge and socioeconomic characteristics. Methods: Our cross-sectional descriptive study investigated 25 districts representing all five administrative regions, three ecological zones, and urban and rural settings. We used structured questionnaires to interview 4,693 married women aged 15–49 years. We assessed UP knowledge by asking women whether they had ever heard about UP, followed by specific questions about symptoms and preventive measures. Descriptive statistics characterized the study population regarding socioeconomic status, assessed how many participants had ever heard about UP, and determined UP knowledge level among participants who had heard about the condition. Simple regression analysis identified a possible association between socioeconomic characteristics, ever heard about UP, and level of UP knowledge. Results: Mean age of participants was 30 years (SD [standard deviation] 7.4), 67.5% were educated, 48% belonged to the advantaged Brahmin and Chhetri groups, and 22.2% were Janajati from the hill and terai zones. Fifty-three percent had never heard about UP. Among women who had heard about UP, 37.5% had satisfactory knowledge. Any knowledge about UP was associated with both urban and rural settings, age group, and education level. However, satisfactory knowledge about UP was associated with administrative region, ecological zones, caste/ethnic group, and age group of women. Conclusion: Fifty-three percent of participants had never heard about UP, and UP knowledge level was satisfactory in 37.% of those who had ever heard about UP. Any knowledge was associated with urban/rural setting, age group, and education level, whereas satisfactory knowledge was associated with geography, caste/ethnic group, and age group. UP-related health promotion programs should target women from all caste/ethnic groups, age groups, and education levels, including urban and rural communities. Keyword: associated factors, knowledge, uterine prolapse, associated factors, Nepal